Analisis Pengawasan Keselamatan Dan Kesehatan Kerja Dinas Transmigrasi Dan Tenaga Kerja Provinsi Sulawesi Tenggara - Rivai, Afrian; Razak, Abdul; Asraf, Asraf (Program Pascasarjana STIE Amkop Makassar, 2023)
The purpose of this research is to know and understand the supervision of occupational safety and health (K3) of the Transmigration and Manpower Office of Southeast Sulawesi Province in realizing the culture of K3 occupational safety and health at PT. Virtue Dragon Nickel Industry (VDNI). The location of this research is PT. Virtue Dragon Nickel Industry (VDNI). The type and amount of data in this study are in the form of primary data obtained through direct interview techniques. While secondary, namely data obtained through literature studies by referring to literature, journals, and various other information related to the problem under study. The data collection methods that will be used in this study are Interviews and Documentation. Data analysis techniques are: Qualitative data analysis is inductive. The results of the study concluded that the supervision of Occupational Safety and Health (K3) by the Transmigration and Manpower Office can realize the culture of Occupational Safety and Health (K3) at PT. VDNI where the implementation process is carried out by applicable regulations such as: (a). The determination of Occupational Safety and Health (K3) supervision standards is carried out by Permenaker No. 33 of 2016 concerning procedures for labor supervision, which includes; planning, implementation, and reporting. (b). Conducting K3 assessment standards by article 50 of Permenaker No. 5 of 2018 concerning Occupational Safety and Health (K3), (c). Comparing the implementation of work between the standards set by the Transmigration and Manpower Office of Southeast Sulawesi and the implementation of Occupational Safety and Health (K3) at PT. VDNI. (e). Conducting work improvements by providing coaching and training such as heavy equipment operator training so that some heavy equipment operator officers have an operator license from the Ministry of Manpower of the Republic of Indonesia. Keywords: Supervision, Safety, and Occupational Health